Effect of Perfluorane on the Amplitude-Frequency Spectrum of Fluctuations in Cerebral Blood Flow in Hemorrhagic Hypotension and During the Reperfusion Period - I. A. Ryzhkov; Yu. V. Zarzhetsky; I. S. Novoderzhkina (Общая реаниматология)
Objective: to use laser Doppler flowmetry (LDF) to investigate the effect of perfluorane on the time course of microhemocirculato ry changes in the rat pial vessels in acute blood loss and after autohemotransfusion.Material and methods. Experiments were car ried out on 31 outbred male rats weighing 300—400 g under anesthesia with intraperitoneal Nembutal 45 mg/kg. The caudal artery was catheterized to measure blood pressure (BP), to sample and reinfuse blood, and to administer infusion solutions. LDF (ЛАКК 02 device, LAZMA, Russia) was used to record blood flow in the pial vessels of the left parietal region (the center coordinates were 3 mm caudal to bregma and 2 mm left of the sagittal suture. A volumefixed acute blood loss model was applied. The goal amount of blood loss was 30% of the circulating blood volume. At 10 minutes after blood sampling, the animals were administered 0.9% NaCl solution (physiologic saline (PS), n=15) or perfluorane (PF), n=16)) in a dose of 3 ml/kg body weight. At 60 minutes following blood sampling, autohemotransfusion was used, after which there was a 60min reperfusion period. The investigators analyzed LDF readings and determined the following indicators: microcirculation index; the maximum amplitudes of blood flow fluctuations in the endothelial, neurogenic, and myogenic frequency ranges by a wavelet analysis. The data were statistically processed using Statistica 7.0 software.Results. Hypovolemia caused a more than 50% reduction in BP; moreover, blood flow in the pial vessels decreased by less than 20% of its baseline level (p<0.05). In the same period, there was an increase in the amplitude of flux motions mainly in the neurogenic (NA) frequency. The differences in microcirculatory parameters between the PS or PF groups were in the retention of higher NA in the PS group throughout hypovolemia; at the same time the groups did not differ in the arterial blood levels of the index of perfusion (IP), рСО2, and lactate. After blood reinfusion and BP elevation, the examined microcirculatory parameters did not dif fer between the groups and were similar to the baseline values, suggesting that there were compensatory changes in the amplitude of flux motions in response to evolving blood loss.Conclusion. The findings suggest that PF versus PS leads to the reduced tension of compensatory mechanisms for cerebral blood flow regulation at a risk for hypoxia during hypovolemia.